INTENSITAS NYERI BERKORELASI DENGAN KEBUTUHAN TIDUR PADA PASIEN POST OPERASI FRAKTUR EKSTREMITAS BAWAH - Nurhayati Syukri; Nur Azizah; Desiana Desiana; Asniah Syamsuddin (Journal Keperawatan, 2023)
Around 80% of postoperative patients complain about pain on the surgical area, the impact of postoperative pain can disrupt a person's sleep needs. This study aims to determine the relationship between pain intensity and the need for sleep in the postoperative of lower extremity fracture patients at Meuraxa Hospital in Banda Aceh. Data were collected for 30 days in the Al-Bayyan 2 and 3 of Surgical Inpatient Rooms at Meuraxa Hospital in Banda Aceh. The research used a correlation method with a cross sectional approach with 43 total respondents. The Numeric Rating Scale (NRS) and the Pittsburgh Sleep Quality Index (PSQI)questionnaires were used  to measure pain scale and sleep needs. Then the data was processed using a computer device. The results of this study showed that pain intensity from 27 respondents (62.8%) of postoperative patients with lower extremity fractures at Meuraxa Hospital Banda Aceh 2022 was at severe  and the need for sleep from 31 respondents (72, 1%) was in a bad category. The bivariate analysis showed that the value of p = 0.004 and ɑ = 0.05 (p value < ɑ) meaning that Ha is accepted. There is a relationship between pain intensity and the need for sleep in postoperative lower extremity fracture patients at Meuraxa Hospital in Banda Aceh.